2012
DOI: 10.3109/09513590.2011.632792
|View full text |Cite
|
Sign up to set email alerts
|

Soluble platelet/endothelial cell adhesion molecule (sPECAM)-1 is increased in polycystic ovary syndrome and related to endothelial dysfunction

Abstract: Striking evidence indicates endothelial impairment in polycystic ovary syndrome (PCOS) but the mechanisms linking PCOS status to cardiovascular risk remain elusive. Platelet/endothelial cell adhesion molecule (PECAM)-1 is a soluble (s) signaling molecule involved in inflammation and angiogenesis with predictive value for endothelial dysfunction in patients at risk. In a prospective, controlled study, sPECAM-1 levels and the relationships to metabolic, inflammatory and vascular PCOS traits were evaluated in 26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…These results indicated that plasma sPECAM-1 levels may be a marker for decreased PECAM-1 protein expression in venous vessels, and be associated with a high risk of thrombosis. This hypothesis was supported by a previous study that detected increased levels of plasma sPECAM-1 in polycystic ovary syndrome (30), which is a predisposing condition for VTE (31).…”
Section: B a Discussionsupporting
confidence: 72%
“…These results indicated that plasma sPECAM-1 levels may be a marker for decreased PECAM-1 protein expression in venous vessels, and be associated with a high risk of thrombosis. This hypothesis was supported by a previous study that detected increased levels of plasma sPECAM-1 in polycystic ovary syndrome (30), which is a predisposing condition for VTE (31).…”
Section: B a Discussionsupporting
confidence: 72%
“…The more pronounced insulin resistance and compensatory hyperinsulinemia, the more efficacious is metformin not only in lowering insulin levels but also in promoting weight loss and alleviating dyslipidemia (33- 35). There is plenty of evidence of metformin favorably influencing cardiovascular risk in PCOS, in monotherapy (36) and combined to oral contraceptives as well (37). According to 27, metformin is not recommended as first-line treatment in PCOS ovulatory dysfunction but may act beneficial as pre-or combination therapy with clomiphene citrate.…”
Section: Management Of Endocrine and Cardio-metabolic Abnormalities Imentioning
confidence: 99%
“…Elevated EMP levels have been associated with cardiovascular and autoimmune diseases, cancer, endocrine and metabolic disorders and, therefore, they are often used as surrogate markers of endothelial dysfunction in these conditions (14). Compared to controls, women with PCOS have increased levels of circulating MPs deriving from endothelial cells, platelets and leukocytes (15,16,17,18). Lifestyle interventions (e.g.…”
Section: Introductionmentioning
confidence: 99%